2018
DOI: 10.15294/biosaintifika.v10i2.15051
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Differentiation of Bone Marrow Mesenchymal-Like Stem Cell Induced by Delonix regia Flowers Extract

Abstract: Stem cell technology has great potential in the effort to cure degenerative diseases. This study was done to determine optimum dose of flamboyant (Delonix regia) flower extract to induce proliferation and differentiation of mice (Mus musculus) bone marrow mesenchymal-like stem cell. Bone marrow cells were collected from mice by aspiration. Cells suspension (1 x 106) were poured into petri dishes containing 2 ml of modified Dulbecco's Modified Eagle's Media (mDMEM) and incubated overnight at 37 °C in a 5% CO2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…The effect of this drug on both blood glucose and pancreatic cell recovery is lower compared to those caused by flamboyant flower extracts. Results obtained in this study, together with those previoulsy presented about the effect of D. regia extract on the proliferation and differentiation of bone originated stem cells (Eriani et al 2018) has showed possible use of the plant extract in diabetes management and therapy, an important contibution in the way to study the antidiabetic exploration of the plant extract for the development of antidiabetic formulation.…”
Section: Degeneration and Necrosis Of Pancreatic β-Cellsupporting
confidence: 68%
See 1 more Smart Citation
“…The effect of this drug on both blood glucose and pancreatic cell recovery is lower compared to those caused by flamboyant flower extracts. Results obtained in this study, together with those previoulsy presented about the effect of D. regia extract on the proliferation and differentiation of bone originated stem cells (Eriani et al 2018) has showed possible use of the plant extract in diabetes management and therapy, an important contibution in the way to study the antidiabetic exploration of the plant extract for the development of antidiabetic formulation.…”
Section: Degeneration and Necrosis Of Pancreatic β-Cellsupporting
confidence: 68%
“…Previous studies have shown the potential of flamboyant flower extract to induce differentiation of mesenchymal stem cells (MSC) into nerve cells (Eriani et al 2018) and osteoblasts (Eriani et al 2020) in vitro. The MSCs, that are almost present in all tissues in the body such as bone marrow cells, adipose tissue, muscle, heart, and lung (Wei et al 2013;Williams & Hare 2011) have potential as immunomodulators and tissue regeneration.…”
Section: Degeneration and Necrosis Of Pancreatic β-Cellmentioning
confidence: 99%
“…The control band was not clear, perhaps due to a pipetting error. The size of the DNA band of the primer β-actin was about 443bp as expected, and the primer β-tubulin 3 was about 700bp, while according to Wang et al, 11 the size of targeted β-tubulin 3 was 55bp. This size difference was probably because the primer design was based on Rattus novergicus, the brown rat, while in this study we used M. musculus.…”
Section: Number Of Differentiated Mesenchymal Stem Cells Into Nerve L...supporting
confidence: 64%
“…The mixture was then sterilized using microfiltration with a diameter of 0.22 μm. 11 Housing and husbandry of animals The male M. musculus mice of the strain BALB/c (eight weeks of age) were acclimated and fed ad libitum with standardized feed for one week under laboratory conditions with a 12 h light-dark cycle, 60% of humidity with 23 o C. To minimize the number of animals, six mice were used with assumption that the number of MSCs from one mouse was enough for one set of repetitions (i.e., with four repetitions in this study, two other mice were prepared for any unexpected event such as if the MSCs did not grow).…”
Section: Preparation Of Dulbecco's Modified Eagle's Medium (Mdmem)mentioning
confidence: 99%
“…The cervical dislocation was carried out in four three-month-old male mice of the Balb-C strain. The method of isolation and primary culture of MSC bone marrow in this study were based on the protocol of Eriani, et al, (2018).…”
Section: Isolation and Primary Culture Of Bone Marrow Mscmentioning
confidence: 99%